PENGARUH DEBT TOQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TERHADAP KEBIJAKAN DIVIDEN - Syaiful, Syaiful (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : Dividend policy is an important thing for the company, because it is a decision whether the profit or profit earned by the company at the end of the year will be distributed to shareholders in the form of dividends or held to increase capital for investment financing in the future, an important thing for the company. because the good or bad capital structure will directly affect the company's operations, including its funding. This study aims to determine the effect of Debt to Equity Ratio and Return on Assets on Dividend Policy in Food and Beverages companies listed on the IDX in 2017-2019. The sample obtained is 10 companies by using purposive sampling. This study uses secondary data and the research method used is multiple linear analysis. The results showed that DER had no significant effect. This is shown from the t-test with the results of t-count 1.183 <1.697 and significant 0.247> 0.05. While ROA has no significant effect on t test results, t count -0.423 < 1.697 and significant 0.975 > 0.05. The coefficient of determination in this study is 0.52, meaning that 52% of the DER and ROA variables explain the Dividend Policy variable and the rest is explained by other variables.